Natural Disaster Preparedness for People with Disabillities: A Scoping Review - Rizky Lukman Saputra; Athaya Zafira Yuflih; Nurasiah Nurasiah; Rita Dewi; Apriyali Apriyali; Baihaki Baihaki; Joko Pitoyo (Universitas Malahayati, 2026)
ABSTRACTNatural disasters are a global threat that significantly impacts vulnerable populations, including people with disabilities. Data from the United Nations Office for Disaster Risk Reduction (UNDRR) indicates that people with disabilities face a two to four times higher risk of injury or death during disasters due to systemic barriers, such as inaccessible emergency information, non-inclusive early warning systems, and inadequate evacuation services. Indonesia, as a country with high disaster risk, underscores the urgency of addressing this issue, especially for the 23.3 million people with disabilities who often face obstacles in accessing disaster preparedness resources. This scoping review aims to explore the literature related to disaster preparedness for people with disabilities, focusing on three main aspects: challenges faced, strategies for enhancing preparedness, and identified research gaps. This study uses the framework. using the Arksey and O’Malley (2005) framework with PRISMA-ScR guidelines. A systematic search was conducted in the PubMed, Scopus, and Sage Journal databases using keywords related to disability and disaster preparedness. Inclusion criteria included English-language articles published between 2015–2025 that focused on disaster preparedness for individuals with physical or mental disabilities. This scoping review identified that people with disabilities face multidimensional challenges in disaster preparedness, including physical barriers (such as mobility and accessibility), social barriers (reliance on caregivers), and systemic barriers (lack of inclusive policies). The analyzed studies indicate that certain types of disabilities—physical, sensory, intellectual/cognitive, and medical dependencies—require different approaches in preparedness interventions. medical dependency—requires a different approach in preparedness interventions. For example, individuals with sensory disabilities need accessible early warning systems, while those with medical dependencies require emergency healthcare infrastructure. Effective intervention strategies include family-based approaches (preparedness toolkits), community preparedness training for people with disabilities, and the development of inclusive evacuation facilities. However, policy implementation remains weak, with minimal involvement of people with disabilities in disaster risk reduction (DRR) planning. Multi-sectoral collaboration is also needed, including the role of community health workers as facilitators and advocates for inclusive policies. Disaster preparedness for people with disabilities requires a multidimensional approach that integrates physical, social, and policy aspects. Targeted strategies, inclusive policy reforms, and community-based interventions are essential to reduce vulnerability. The role of nursing and community health practices is important in building a fair and inclusive preparedness system. Keywords: Disaster Preparedness, People with Disabilities, Emergency Management. ABSTRAK Bencana alam merupakan ancaman global yang berdampak signifikan terhadap populasi rentan, termasuk penyandang disabilitas. Data dari United Nations Office for Disaster Risk Reduction (UNDRR) menunjukkan bahwa penyandang disabilitas memiliki risiko cedera atau kematian dua hingga empat kali lebih tinggi saat bencana akibat hambatan sistemik, seperti informasi darurat yang tidak aksesibel, sistem peringatan dini yang tidak inklusif, dan layanan evakuasi yang kurang memadai. Indonesia sebagai negara dengan risiko bencana tinggi mempertegas urgensi penanganan isu ini, terutama bagi 23,3 juta penyandang disabilitas yang sering menghadapi kendala dalam mengakses sumber daya kesiapsiagaan bencana. Scoping review ini bertujuan untuk mengeksplorasi literatur terkait kesiapsiagaan bencana bagi penyandang disabilitas, dengan fokus pada tiga aspek utama: tantangan yang dihadapi, strategi peningkatan kesiapsiagaan, serta kesenjangan riset yang teridentifikasi. Studi ini menggunakan kerangka kerja Arksey dan O’Malley (2005) dengan panduan PRISMA-ScR. Pencarian sistematis dilakukan di database PubMed, Scopus, dan Sage Journal menggunakan kata kunci terkait disabilitas dan kesiapsiagaan bencana. Kriteria inklusi meliputi artikel berbahasa Inggris terbitan tahun 2015–2025 yang berfokus pada kesiapsiagaan bencana bagi penyandang disabilitas fisik atau mental. Scoping review ini mengidentifikasi bahwa penyandang disabilitas menghadapi tantangan multidimensi dalam kesiapsiagaan bencana, meliputi hambatan fisik (seperti mobilitas dan aksesibilitas), sosial (ketergantungan pada caregiver), dan sistemik (kurangnya kebijakan inklusif). Studi-studi yang dianalisis menunjukkan bahwa jenis disabilitas tertentu—fisik, sensorik, intelektual/kognitif, dan ketergantungan medis—memerlukan pendekatan berbeda dalam intervensi kesiapsiagaan. Misalnya, penyandang disabilitas sensorik membutuhkan sistem peringatan dini yang aksesibel, sementara mereka dengan ketergantungan medis memerlukan infrastruktur kesehatan darurat. Strategi intervensi yang efektif meliputi pendekatan berbasis keluarga (toolkit kesiapsiagaan), pelatihan komunitas kesiapsiagaan bagi penyandang disabilitas, dan pengembangan fasilitas evakuasi inklusif. Namun, implementasi kebijakan masih lemah, dengan minimnya pelibatan penyandang disabilitas dalam perencanaan pengurangan risiko bencana (DRR). Diperlukan juga kolaborasi multisektoral, termasuk peran tenaga kesehatan komunitas sebagai fasilitator dan advokat kebijakan inklusif. Kesiapsiagaan bencana bagi penyandang disabilitas memerlukan pendekatan multidimensi yang mengintegrasikan aspek fisik, sosial, dan kebijakan. Strategi yang tepat sasaran, reformasi kebijakan inklusif, serta intervensi berbasis komunitas sangat penting untuk mengurangi kerentanan. Pentingnya peran keperawatan dan praktik kesehatan komunitas dalam membangun sistem kesiapsiagaan yang adil dan inklusif. Kata Kunci: Kesiapsiagaan Bencana, Penyandang Disabilitas, Manajemen Darurat.